2003
DOI: 10.1103/physrevlett.91.115701
|View full text |Cite
|
Sign up to set email alerts
|

Does the Arrhenius Temperature Dependence of the Johari-Goldstein Relaxation Persist aboveTg?

Abstract: Dielectric spectra of the polyalcohols sorbitol and xylitol were measured under isobaric pressures up to 1.8 GPa. At elevated pressure, the separation between the alpha and beta relaxation peaks is larger than at ambient pressure, enabling the beta relaxation times to be unambiguously determined. Taking advantage of this, we show that the Arrhenius temperature dependence of the beta relaxation time does not persist for temperatures above T(g). This result, consistent with inferences drawn from dielectric relax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
112
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(127 citation statements)
references
References 30 publications
(33 reference statements)
14
112
0
1
Order By: Relevance
“…From the energy landscape point of view 32,[45][46][47] , this description would correspond to the existence of different subminima of similar energy barriers that the system can explore with relaxation times of the order of 100-1,000 s. The experimental detection of such local atomic motion in the macroscopically large scattering volume suggests the existence of many different independent groups of atoms, which move rapidly among the sub-minima of a deep local minimum. Albeit a similar description has been often associated with secondary relaxation processes active in the glassy state 1,53,[66][67][68] , we ruled out this hypothesis because in this case the correlation curves would decay towards a long nonergodic plateau, indicating the existence of a much slower final decay associated with the structural relaxation process. Differently, our data display a full decorrelation to zero of the density fluctuations, suggesting the main structural relaxation to be responsible of the observed decorrelation at the atomic level.…”
Section: Discussionmentioning
confidence: 93%
“…From the energy landscape point of view 32,[45][46][47] , this description would correspond to the existence of different subminima of similar energy barriers that the system can explore with relaxation times of the order of 100-1,000 s. The experimental detection of such local atomic motion in the macroscopically large scattering volume suggests the existence of many different independent groups of atoms, which move rapidly among the sub-minima of a deep local minimum. Albeit a similar description has been often associated with secondary relaxation processes active in the glassy state 1,53,[66][67][68] , we ruled out this hypothesis because in this case the correlation curves would decay towards a long nonergodic plateau, indicating the existence of a much slower final decay associated with the structural relaxation process. Differently, our data display a full decorrelation to zero of the density fluctuations, suggesting the main structural relaxation to be responsible of the observed decorrelation at the atomic level.…”
Section: Discussionmentioning
confidence: 93%
“…This phenomenon was termed "excess wing" in [21] to account for the intensity in excess of the highfrequency flank of the α-relaxation peak, connected with this spectral feature. In contrast, xylitol (T g ≈ 248 K) is known to exhibit a well-pronounced secondary relaxation ("type B" glass former [17]) [22,23,24,25,26]. From the results reported in [26], by using a criterion [18] for genuine Johari-Goldstein (JG) relaxations [3] based on Kia Ngai's coupling model [27], it can be concluded that the β-relaxation in xylitol indeed is of JG type.…”
Section: Resultsmentioning
confidence: 99%
“…However, close to T g (1000/T g ≈ 4.1 K -1 ) it seems to become nearly constant and even to exhibit a minimum. Taking into account some recent reports [24,38,45,46], one may speculate that this could be a general behavior of type B glass formers. It can be described by the socalled "minimal model" (MM) by Dyre and Olsen [47].…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Dielectric and mechanical spectroscopies have shown a peak in the isothermal loss spectra or a peak in the plot of loss at a fixed frequency against temperature, and a broad inverted sigmoid-shape decrease in the permittivity and increase in the storage modulus. When only a broad shoulder or an apparent wing has been observed instead of a peak, the ␤-relaxation peak has been experimentally resolved by aging the glass, 21 by using high pressures, 25 by adding a second component, 29 and by a detailed analysis of the spectra. 19 To distinguish it from other ␤-relaxation processes, e.g., the mode-coupling theory's ␤ relaxation and ␤ relaxations involving intramolecular barriers, the above-mentioned relaxation has been known as the Johari-Goldstein ͑JG͒ relaxation.…”
Section: Introductionmentioning
confidence: 99%
“…27,40 Characteristics of the JG relaxation have been recently reviewed. 1,2 Briefly, ͑i͒ the ␣-relaxation process appears to evolve from it at a temperature where its relaxation rate is in the microsecond range, 16,41 a temperature termed as the Donth temperature ͑for the merging of the ␣-and ␤-relaxation processes͒, ͑ii͒ the height of the dielectric relaxation peak Љ m,JG and its relaxation strength ⌬ JG decreases on structural relaxation or aging of a glass, [8][9][10]12,24,28 ͑iii͒ its spectral half width, which is much larger than that of the ␣-relaxation process, increases with a decrease in the temperature, [6][7][8][9][10][12][13][14][15]23,26,29 ͑iv͒ its relaxation rate follows an Arrhenius temperature dependence at temperatures [6][7][8][9][13][14][15][16]18,19,25,[29][30][31]42 far below the Donth temperature, with an activation energy and preexponent compatible with that for hindered molecular reorientation, ͑v͒ the ⌬ JG against temperature plot shows a feature similar to that of enthalpy relaxation on heating, 17,18,26 and an elbow-shape change in the slope occurs a...…”
Section: Introductionmentioning
confidence: 99%